Job Satisfaction in Joint Venture Hotels in China: An Organizational Justice Analysis - Leung, Kwok; Smith, Peter B.; Wang, Zhongming; Sun, Haifa (Journal of International Business Studies, 1996)
In a survey of local employees of joint venture hotels in China, it was found that procedural and performance-based distributive justice was related to job satisfaction, but interactional justice was not. Comparison with other local employees was related to job satisfaction, but comparison with overseas employees was not. Senior managers reported a lower level of procedural and interactional justice, and senior managers and supervisors regarded their pay as less fair in comparison with local employees in state-owned hotels. Employees who worked with overseas Chinese and Japanese expatriates were less satisfied than those who worked with expatriates from the West, and this difference was explainable in terms of differences in perceived distributive justice.